Revealing the Cytotoxicity of Residues of Phosphazene Catalysts Used for the Synthesis of Poly(ethylene oxide) - Xia, Yening; Shen, Jizhou; Alamri, Haleema; Hadjichristidis, Nikos; Zhao, Junpeng; Wang, Yucai; Zhang, Guangzhao (Biomacromolecules, 2017)
We herein report a case study on the toxicity of residual catalyst in metal-free polymer. Eight-arm star-like poly(ethylene oxide)s were successfully synthesized via phosphazene-catalyzed ring-opening polymerization of ethylene oxide using sucrose as an octahydroxy initiator. The products were subjected to MTT assay using human cancer cell lines (MDA-MB-231 and A2780). Comparison between the crude and purified products clearly revealed that the residual phosphazenium salts were considerably cytotoxic, regardless of the anionic species, and that the cytotoxicity of more bulky t-BuP4 salt was higher than that of t-BuP2 salt. Such results have therefore put forward the necessity for removal of the catalyst residues from PEO-based polymers synthesized through phosphazene catalysis for biorelated applications and for the development of less or nontoxic organocatalysts for such polymers.